An Introduction to the STRAMERS Model for Graduate Biology Education: Development and Acceptability for Sustainable Instruction - Camara, Jun S. (International Journal of Biology Education Towards Sustainable Development, 2024)
Revision of the Policies, Standards, and Guidelines in the offering of graduate education in the Philippines necessitated curricular innovations particularly in integrating research in graduate courses. This study aimed to introduce and propose STRAMERS Model for utilization in science education by graduate schools in local colleges and state universities in the Philippines. The requirement via this model at the end of a semester is a systematic review output or SYRO which was content analyzed in two stages, i.e. first for its general features as an IMRAD article to evidence feasibility and to describe the raw skills of graduate students in writing a SYRO and second for its features relative to the PRISMA 2020 Updated Guidelines to evidence its adherence and to describe the opportunities for improvement in this and in succeeding SYROs. An acceptability test for both users and expert validators was conducted. Results showed that the SYROs have manifested the adherence to format of academic publications and its basic elements to adhere to latest review models which leads the researcher to the conclusion that the use of SYROs could be an alternative mechanism in integrating research in science graduate courses in response to curricular innovations brought about by CMO No. 15, s. 2019 and recommending the utilization of the STRAMERS Model in implementing this innovation. Further, prospective users rated the Model with 4.4 level of acceptability which means very highly acceptable. Furthermore, expert’s insights on the Model reveals its novelty in the field of publication hence was recommended for adoption among graduate schools in the Philippines because of its unique features as well as ability for continuous syllabus refinement.